2016
DOI: 10.1364/josab.33.0000b5
|View full text |Cite
|
Sign up to set email alerts
|

Design of infrared and ultraviolet Raman lasers based on grating-coupled integrated diamond ring resonators

Abstract: We investigate the opportunities of Raman lasers based on integrated single-crystal diamond ring resonators. We model continuous-wave (CW) Raman lasing action while taking into account the lasing directionality, the linear and nonlinear losses, and the coupling of the fields between the bus and ring sections of racetrack-shaped diamond ring resonators. Besides designing the ring resonators for a short-wavelength infrared (SWIR) and an ultraviolet (UV) Raman laser, we also design diamond gratings to couple ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
4
1
Order By: Relevance
“…With a Raman threshold of 20 mW, we calculate [9] an effective Raman gain value of 3.2 cm GW −1 . This is lower than previous values for diamond at these wavelengths (> 10 cm GW −1 [1]), and can be attributed to imperfect confinement (74% of the optical power is in the diamond core) and Raman gain dependence on the orientation of the crystal axes with respect to the propagation/polarization direction [1,20]. The near-threshold data implies an external conversion efficiency of 1.7%, corresponding to an internal efficiency The studied pump resonance shows a total quality factor Q ∼301,000 at 750.88 nm, corresponding to a Stokes resonance of Q ∼85,000 at 834.34 nm.…”
Section: Optical Measurementscontrasting
confidence: 65%
See 1 more Smart Citation
“…With a Raman threshold of 20 mW, we calculate [9] an effective Raman gain value of 3.2 cm GW −1 . This is lower than previous values for diamond at these wavelengths (> 10 cm GW −1 [1]), and can be attributed to imperfect confinement (74% of the optical power is in the diamond core) and Raman gain dependence on the orientation of the crystal axes with respect to the propagation/polarization direction [1,20]. The near-threshold data implies an external conversion efficiency of 1.7%, corresponding to an internal efficiency The studied pump resonance shows a total quality factor Q ∼301,000 at 750.88 nm, corresponding to a Stokes resonance of Q ∼85,000 at 834.34 nm.…”
Section: Optical Measurementscontrasting
confidence: 65%
“…Accordingly, lasing for a TE pump occurs over a relatively larger bandwidth, and lasing for a TM pump occurs in two distinct wavelength regions. The output is likely to be TE-polarized, due to the lower quality factors for TM resonances and forbidden TM-TM transition for [001]-oriented diamond [1,20].…”
Section: Optical Measurementsmentioning
confidence: 99%
“…Typically, Stokes scattering alone is not useful for upconverting IR to UV or visible light (it downconverts or redshifts the wavelength), but anti-Stokes scattering (which occurs in conjunction with Stokes scattering) can be used for upconversion. This is typically efficient in systems where there is a very large intensity, such as high-Q resonators where photons circulate with a very long lifetime, or high confinement, as in plasmonic nanoparticles or structures [60][61][62][63][64]. Stimulated Raman scattering is a process where the pump and Stokes wavelengths are introduced into the material to generate an enhanced Raman response where energy is transferred from the pump wavelength to the Negative uniaxial (n e < n o ) Stokes wavelength.…”
Section: Other Effects: Raman Scattering Brillouin Scattering Supermentioning
confidence: 99%
“…Instead, they are induced by scattering which is mainly attributed to the sidewall roughness of the waveguides. We note that the scattering loss tends to be higher at shorter wavelengths: a recent study on diamond waveguides showed that at UV wavelengths the scattering loss can be up to two orders of magnitude larger than at IR telecom wavelengths [10]. Hence, to reduce the waveguide losses at the three short wavelengths considered in our paper, the waveguides' sidewall roughness should be further decreased and this could be achieved through technological improvements both regarding SCD sample quality and waveguide fabrication.…”
Section: Discussionmentioning
confidence: 88%
“…In the visible (VIS) spectral domain, a recent study has numerically demonstrated SCD waveguides as more suitable candidates than Si 3 N 4 waveguides for VIS supercontinuum generation (SCG) due to SCD's higher refractive index (2.412 at 635 nm [7]) allowing stronger light confinement and more possibilities for dispersion engineering [8]. In the UV spectral domain, studies have numerically demonstrated the promises of using SCD for wavelength conversion in the UV range by means of Kerr and Raman-resonant wave-mixing processes [9,10]. Possible applications of SCG and wavelength conversion in diamond waveguides in the VIS-UV domain include short-wavelength spectroscopy and fluorescence measurements [11][12][13] integrated on a chip.…”
Section: Introductionmentioning
confidence: 99%